Effectiveness of Osteoarthritis Management Program (OAMP) on the Level of Knowledge and Practice Regarding Self-Management Among Elderly with Osteoarthritis - Pratima Sapkota; Venkatesan Balu; Sonia Kamei; Yumnam Sushma Devi (Wolters Kluwer Medknow Publications, 2024)
Objectives: To assess the effectiveness of osteoarthritis management program (OAMP) on the level of knowledge and practice regarding self-management among elderly with OA. Materials and Methods: A quasi-experimental study was conducted among 60 elderly with osteoarthritis (OA) from March 1, 2021, to March 29, 2021. A community-based survey was conducted to identify the elderly with OA, and 60 persons were selected by using simple random technique. Knowledge was assessed through structured questionnaire, and non-observational checklist was used for Practice. OAMP was conducted to impart knowledge and practice skills. Results: The study findings showed that the majority of the participants had inadequate knowledge and poor practice before the intervention, whereas, after the implementation of OAMP, the maximum number of participants had adequate knowledge and good practices. The knowledge mean score increased from 52% to 86.7% and practices from 43.8% to 88.5%. There was a significant hike in the difference between the mean pre-test and post-test scores at P < 0.001 level. Conclusion: The present study proves that the use of OAMP is effective in increasing the level of knowledge and also in improving the practices among participants which help in self-management of OA and result in improvement in the level of physical function.